2008
DOI: 10.3748/wjg.14.1204
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of a new cell line derived from human colorectal laterally spreading tumor

Abstract: CONCLUSION:We established and characterized a colorectal cancer cell line, LST-R1 and LST-R1 has an obvious malignant tendency, which maybe partially attributed to the changes of the expression of some adhesion molecules, such as E-cadherin. It is also a versatile tool for exploring the original and progressive mechanisms of laterally spreading tumor and the early colon cancer genesis. INTRODUCTIONTwo routes have been described that can lead to colon carcinogenesis: one is the adenoma-carcinoma model, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Thus, it is likely that after a longer period in vitro, the rate of proliferation will slow down, because this cell line has not been reported to result in tumor formation (10,11). Cell line RMNE6 was also immortalized using the temperature-sensitive mutant of the SV40 large antigen, and it shows a fourfold decrease in cell proliferation (raw data) between 33°C and 39.5°C after 6 days in vitro (41), comparable to what we observed with cell line M213-2O CL-4.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Thus, it is likely that after a longer period in vitro, the rate of proliferation will slow down, because this cell line has not been reported to result in tumor formation (10,11). Cell line RMNE6 was also immortalized using the temperature-sensitive mutant of the SV40 large antigen, and it shows a fourfold decrease in cell proliferation (raw data) between 33°C and 39.5°C after 6 days in vitro (41), comparable to what we observed with cell line M213-2O CL-4.…”
Section: Discussionsupporting
confidence: 83%
“…In another study, Thompson found that cell line CN 1.4 releases 30% of its total GABA content after a high K + stimulus (38). Wang et al (41) reported on another GABA-producing cell line, RMNE6, established from E13 rat ventral mesencephalon cells, that has 4.13 ± 0.31 μmol/l GABA in the cytoplasm. Cell line M213-2O CL-4 has 239.68 μmol/g protein of intracellular GABA, and after high potassium stimulation it releases 1.7% (4.12 μmol/g protein) of this GABA.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that tumor cell lines Lan-1, HeLa and Co115 are telomerase-positive (27). A study describing the establishment of the LST cell line demonstrated that the histopathology of a nude mouse xenograft tumor was a poorly differentiated adenocarcinoma and cells cultured from the xenograft tumor had the same properties as the original cell line (28). Thus, the LST cell line has higher malignancy than normal adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…The primary normal colon epithelium cells, human CRC cell lines LST,20 SW1116, HCT1116, HT29, SW480, SW620 and LoVo were cultured in RMPI containing 10% FBS. Total cell lysates were extracted by PBSTDS (100 ml 10 × PBS, 10 ml 100% Triton X 100, 5 g nadeoxycholate, 1 g SDS, 1 nM EDTA, up to 1,000 ml/day H 2 O) on ice and were centrifuged at 13,000 rpm at 4°C for 15 min.…”
Section: Methodsmentioning
confidence: 99%